TINJAUAN YURIDIS ATAS GRATIFIKASI YANG DIPERKARAKAN DI PENGADILAN TINDAK PIDANA KORUPSI SAMARINDA DALAM PERSEPEKTIF HUKUM PIDANA INDONESIA - Beni Fernandes Hibur (Universitas 17 Agustus 1945 Samarinda, 2015)
ABSTRACTION Gratifikasi is not type glare at but as element glare at, as for glaring at of own is receiver of Gratifikasi which oppose against its obligation and its duty, Congeniality of GRATIFIKASI there are Clarification of Section 12B Sentence ( 1) UU No.31 Year 1999 as altered with UU No.20 Year 2001, that :